Anthraquinone substituents modulate ionic hydrogen-bonded organic frameworks to achieve high ionic conductivity for alkali metal ions - Chen, Xu-Yong; Fei, Guiqiang; Bai, Xiang-Tian; Qi, Simeng; Cao, Xiao-Jie; Gao, Yi-Da; Luo, Xin; Cao, Li-Hui (Chemical communications (Cambridge, England), 2025)
Herein, we report two charge-assisted hydrogen-bonded organic frameworks ( iHOF-24 and iHOF-25 ) with 3D/2D hydrogen-bonding networks, which exhibit high ionic conductivity for alkali metal ions. Among them, the conductivity of Li + is higher than that of Na + and K + , and the ionic conductivities of Li@ iHOF-24 and Li@ iHOF-25 at 30 °C were 9.44 × 10 −5 and 9.85 × 10 −5 S cm −1 . This change is attributed to the distance between neighboring carbonyl groups in iHOF-24 and iHOF-25 , as well as the radius of the loaded alkali metal ions. In this study, we show that iHOF-24 and iHOF-25 exhibit high ionic conductivity for alkali metal ions. At 30 °C, the Li + conductivities of iHOF-24 and iHOF-25 were 9.44 × 10 −5 and 9.85 × 10 −5 S cm −1 , which is higher than that of Na + and K + .